Effect of Some Drugs (Painkiller and Anti-Inflammatory) on Antibiotic Resistance Genes (vim, imp, ndm, oxa48 and aac(6)) in Proteus Mirabilis - Mohsin, Mohsin Rasheed; AL-Rubaii, Bahaa Abdullah Laftaah (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Proteus mirabilis is gram-negative bacteria that is considered responsible for urinary tract infections (UTIs), especially catheter-associated urinary tract infections. The samples of urine (119) were collected from Baghdad hospitals. Proteus spp was recognized by morphology, the Vitek-2 compact system, and the 16SrRNA gene. Antibiotic susceptibility test was also done using the vitek-2 system. The antibiotic resistance genes vim, imp, ndm, oxa48 and aac(6) were amplified using PCR. The Results were shown out of 35 isolates belonging to P. mirabilis, they appeared highest resistance against minocycline, ticarcillin, trimethoprim/sulfamethoxazole, and ticarcillin/ clavulanic with 71.40 %, 68.57%, 65.70% and 57.10% respectively; while, they were sensitive to meropenem and piperacillin/ tazobactam with 2.85 %and 5.57% respectively. Seven isolates were classified as XDR, and the two strongest isolates of them were selected (no 90 and no 99). Only The aac(6) gene appeared positive band at size (395bp) in both isolates while other genes(vim,imp,ndm,oxa48) were not detected in both of the isolates. RT-PCR revealed a down-regulation at 0.015 and 0.485 folding change in gene expression of the aac(6) gene under the effect of olfen and dexamethasone; while it showed Up-regulation at 3.245, 3.55 and 3.22 folding change in gene expression under the effect of paracetemol, piroxicam and nefopam respectively. From the above finding, concluded that each of these drugs a had different effect on the aac(6) gene whether it is up regulation or down regulation. wither it up regulation or down regulation